PH responsive highly branched poly(N-isopropylacrylamide) with trihistidine or acid chain ends. Issue 75 (28th July 2016) - Swift, T.; Lapworth, J.; Swindells, K.; Swanson, L.; Rimmer, S.
Abstract : Thermally responsive highly branched poly( N -isopropyl acrylamide)s (HB-PNIPAM) were prepared and end-functionalised to give polymers with acid or trihistidine end groups. ​The ionisation of the end groups affects the swelling of desolvated globules. Abstract : Thermally responsive highly branched poly( N -isopropyl acrylamide)s (HB-PNIPAM) were prepared and end-functionalised to give polymers with acid or trihistidine end groups. These polymers exhibit a broad coil-to-globule transition across a wide temperature range which can be measured using covalently attached fluorescent tags. The acid chain ends provided a material with a distinct change in solution behaviour at pH close to the p K a of the carboxylate group. At pH 11 this polymer did not show a cloud point up to 50 °C but fluorescence measurements on the labelled polymers showed that a coil to globule transition did take place. The globular state, above the LCST, appeared to be more swollen if the end group carried charge then when it was uncharged. A polymer with trihistidine and free carboxylate chain ends, which contained multiple charges at various pH, did show LCSTs at all pH and the polymer globule was shown to be swollen at each pH.